PENGARUH MEDIA INTERAKTIF KAHOOT DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SMA NEGERI 2 RANTAU UTARA - Fadhilah, Sri (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to see the effect of Kahoot interactive media in increasing student learning motivation at SMA Negeri 2 Rantau Utara. The research method used is Classroom Action Research (CAR). Classroom Action Research was conducted at SMA Negeri 2 Rantau Utara. The subjects in this study were students of class XII IIS 3 SMA Negeri 2 Rantau Utara in the 2024/2025 academic year with a total of 35 students. The results of the study showed that there was a significant increase in the application of Kahoot interactive media on student learning motivation, starting from the pre-action stage by 40%, at the cycle I stage by 65%, and at the cycle II stage by 92%. Therefore, interactive learning media in the form of Kahoot is very influential in increasing student learning motivation because students will learn in a fun way so that it can involve student activity in the learning process, increase interaction between students and teachers, involve student emotions, and students can show their satisfaction in the learning process so that they have the awareness to continue to improve their learning process and increase their insight.